Investigating the adaptability and implementation of computational design methods in concept design taking plasterboard opportunities for dimensional coordination and waste reduction as a case study - Omar Majzoub; M. Hank Haeusler; Sisi Zlatanova (Frontiers of Architectural Research, 2023)
Construction material offcuts is a data problem that can largely be avoided by dimensional coordination during concept design. Besides the environmental benefits, early phase coordination is beneficial to the overall design process as it integrates information not typically considered until later in the design process. However, taking reality-changing actions is often challenged by uncertainty, time constraints, and lack of integration of available tools. Acknowledging the potential of computational design in enabling architects to manage design and coordination complexities and taking plasterboard opportunities for dimensional coordination, the paper presents a review and assessment of the existing methods to interrogate what, when, and how are these adaptable to the task. The study shows that ML-based methods outperform other methods and concludes that leveraging computational design powers to reduce offcuts is not a question of a tool, but one of a strategy. Eventually, the future steps to achieving such a strategy are discussed.